The Research of Aesthetics of Type as Image in Motion-Targeting Video Poetics at Type Motion: Type as Image in Motion Exhibition in Taiwan - Chen, Chih Ho; Hsieh, Sheng-Min (Advances in Social Sciences Research Journal, 2020)
Characters are signs and symbols that record our thoughts and feelings and allow the documentation of events and history. Later, the appearance of motion images marked a new milestone in the use and application of characters. Not only were the original function of characters improved and enhanced, text that integrate sound and images are also able to communicate much more diverse and abundant information. This technique is commonly found in cinema, television, advertisement, and animation. Thanks to technological advances, the combination of characters, texts, or types and images once again changed how we read. It has also created new meaning for our time. Today, type image seems to have achieved an aesthetic autonomy of their own. This has a profound impact on image and art creation and human communication. The emergence of cinema art in the late 19th century brought motion into written media and greatly expanded the possibilities of art. In today’s world of instant communication media, text and images face unprecedented changes. Chinese characters are one of the most ancient writing systems in human history. Unlike western alphabet, each Chinese character has its own form, sound, and meaning. Chinese characters are a highly figurative cultural element. This essay takes Chinese characters and the works featured in the concrete poetry/sound poetry and fragment poetry categories in the National Taiwan Museum of Fine Arts “Type Motion: Type as Image in Motion” exhibition as the subject of study to examine the history of text and media and changes in the way we deliver information and communicate. This essay also provides an analysis of the relationship between text and motion image and the interdependency between culture and technology and media. The connections and differences between Chinese characters in different time and space is also investigated to highlight the uniqueness of the characters as a medium, its application in motion writing techniques and aesthetic forms. This essay focuses on the following four topics: Artistic expression and styles related to the development of type as image in motion. Video poetics: the association between poetics and video images, poetic framework, and analysis of film poetry. Structure, format, characteristics, and presentation of meaning in concrete poetry/sound poetry, and fragment poetry. how Chinese characters are used in Taiwan and the aesthetic features of type through the exhibited works.